A multiplex PCR mini-barcode assay to identify processed shark products in the global trade - Cardeñosa, Diego; Fields, Andrew; Abercrombie, Debra; Feldheim, Kevin; Shea, Stanley K. H.; Chapman, Demian D. (PloS one, 2017)
Protecting sharks from overexploitation has become global priority after widespread population declines have occurred. Tracking catches and trade on a species-specific basis has proven challenging, in part due to difficulties in identifying processed shark products such as fins, meat, and liver oil. This has hindered efforts to implement regulations aimed at promoting sustainable use of commercially important species and protection of imperiled species. Genetic approaches to identify shark products exist but are typically based on sequencing or amplifying large DNA regions and may fail to work on heavily processed products in which DNA is degraded. Here, we describe a novel multiplex PCR mini-barcode assay based on two short fragments of the cytochrome oxidase I (COI) gene. This assay can identify to species all sharks currently listed on the Convention of International Trade of Endangered Species (CITES) and most shark species present in the international trade. It achieves species diagnosis based on a single PCR and one to two downstream DNA sequencing reactions. The assay is capable of identifying highly processed shark products including fins, cooked shark fin soup, and skin-care products containing liver oil. This is a straightforward and reliable identification method for data collection and enforcement of regulations implemented for certain species at all governance levels.